Optimalisasi Produktivitas Tenun Troso Melalui Transfer Teknologi dan Pemasaran Digital - Hidayati, Nor; Maori, Nadia Annisa; Azzat, Noor Nailie (Universitas PGRI Semarang, 2025)
Troso weaving is a distinctive craft product from Troso Village Pecangaan District, Jepara Regency that contributes significantly to the local economy. This weaving is traditionally made on a wooden loom and the manufacturing process required a high level of skill from the operator making it a creative and potentially profitable home industry for community benefit. This community service focuses on the Troso Agung Berkah Weaving Communityt. The old wooden loom as call as the gedokan had a daily production capacity of 2-3 pieces of fabric and a monthly production capacity of approximately 60-70 pieces of fabric that still away to fulfill the demand. This community service aims to increase production capacity through technological advancements by modifying the gedokan wooden loom with transfer technology using dynamo and additional wheels to allow the machine to operate automatically and also to improve competitiveness through digital marketing training based on e-commerce platform as marketing strategy. The first result of this community service is fourfold increase in production capacity with the modified gedokan wooden loom compared to the previous manual gedokan wooden loom and strengthen the skills of partners to implement digital marketing based on e-commerce by utiizing website thus supporting the sustainability of the Troso weaving industry amid global competition.Â